Elderly Quality of Life in Tehran\'s District Two - Fardin Alipour; Homeyra Sajadi; Ameneh Foruzan; Akbar Biglarian; Ali Jalilian (University of Social Welfare & Rehabilitation Sciences, 2008)
Objectives: The world population is graying increasingly and in the most countries, aging is seen as a critical issue. Aging is a natural process In human life and comes out from gradual erosion of vital organs. age, sex and ethnicity as individual factors and social, cultural and economical traits influence the aging time and grade. as the elderly quantity and number increases, attention to living quality in the elderly and determine of influential factors to correct and comprehensive policy making regarding this people has an importance. In this article we study the quality of life status in district's 2 elderly (Tehran). Methods & Materials: Study is a cross-sectional, analytical type that needed information has gathered by elderly specific questionnaire (lipad) and background variables checklist, in a 100 person sample. Kolmogrof and Smimof's (K-S) test and One Way Anova and T-test have used for data analyzing. Results: Sample comprised from 70 men and 30 women and the most of subjects were between 60-70 years old, (M=70) for men and (M=69) for women. There was an significant difference between men and women in all dimensions of quality of life (P<0.05) and the men were high in all dimensions of quality of life. those who were married and high educated and had their own housing were high in quality of life. Conclusion: The elderly quality of life is under the influence of various factors that determining and finding of those factors, is very important in better planning regard to this class of society and their empowerment.